Pemaknaan Penonton Remaja di Jakarta terhadap Operasi Plastik dalam Drama Korea My ID is Gangnam Beauty - Nurul Fauziah; Ratna Puspita (IAI Darussalam, 2022)
This study aims to explore the audience receptions, focusing on adolescents aged 10-24 years in Jakarta, about plastic surgery in the Korean drama